2015
DOI: 10.1038/ng.3437
|View full text |Cite
|
Sign up to set email alerts
|

Genetic fine mapping and genomic annotation defines causal mechanisms at type 2 diabetes susceptibility loci

Abstract: We performed fine-mapping of 39 established type 2 diabetes (T2D) loci in 27,206 cases and 57,574 controls of European ancestry. We identified 49 distinct association signals at these loci, including five mapping in/near KCNQ1. “Credible sets” of variants most likely to drive each distinct signal mapped predominantly to non-coding sequence, implying that T2D association is mediated through gene regulation. Credible set variants were enriched for overlap with FOXA2 chromatin immunoprecipitation binding sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
277
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 385 publications
(297 citation statements)
references
References 75 publications
18
277
0
2
Order By: Relevance
“…83,85 Increasing refinement of regulatory annotation has brought more precise localization of these global regulatory effects, for example, emphasizing specific transcription factor genes (such as FOXA2 [MIM: 600288]). 86 These patterns of tissue-specific genomic enrichment tie in with studies of the physiological correlates of T2D risk alleles, as observed in physiological data from non-diabetic subjects; these have indicated that, whereas some T2D risk alleles have a primary effect on insulin action, most appear to be associated with reduced insulin secretion. 87 These approaches have generated some notable advances, for example, cis-expression mapping has highlighted KLF14 (MIM: 609393) as the mediator of a chromosome 7 T2D signal that is associated with insulin resistance and hyperlipidemia (appropriately, this expression signal is specific to adipose tissue).…”
Section: Type 2 Diabetesmentioning
confidence: 64%
“…83,85 Increasing refinement of regulatory annotation has brought more precise localization of these global regulatory effects, for example, emphasizing specific transcription factor genes (such as FOXA2 [MIM: 600288]). 86 These patterns of tissue-specific genomic enrichment tie in with studies of the physiological correlates of T2D risk alleles, as observed in physiological data from non-diabetic subjects; these have indicated that, whereas some T2D risk alleles have a primary effect on insulin action, most appear to be associated with reduced insulin secretion. 87 These approaches have generated some notable advances, for example, cis-expression mapping has highlighted KLF14 (MIM: 609393) as the mediator of a chromosome 7 T2D signal that is associated with insulin resistance and hyperlipidemia (appropriately, this expression signal is specific to adipose tissue).…”
Section: Type 2 Diabetesmentioning
confidence: 64%
“…Studies have shown that dysregulation of islet enhancers is relevant to the underlying mechanisms of T2D 22 and a recent examination of some of the previously found T2D loci have been found to overlap with FOXA2-bound sites. 32 The cosmopolitan T2D location interval near ACTL7B overlapped with chromatin peaks for CD14 þ monocytes and included an eQTL for KLF4 and EPB41L4B. KLF4 is highly expressed in CD14 þ monocytes and belongs to the Krüppel-like factor (KLF) family that consists of transcription factors that can activate or repress different genes involved in processes such as differentiation, development, and cell cycle progression, with several of these proteins implicated in glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, successive waves of T2D GWAS -featuring ever larger samples, progressively denser genotyping arrays supplemented by imputation against more complete reference panels, and richer ethnic diversity -have delivered >80 robust association signals [2][3][4][5][6][7][8] . However, in these studies, the alleles interrogated for association are predominantly common (minor allele frequency [MAF]>5%), and with limited exceptions 7,9 , the variants driving known association signals are also common, with individually-modest impacts on T2D risk [2][3][4][5][6][7][8]10 . Variation at known loci explains only a minority of observed T2D heritability 2,3,11 .…”
mentioning
confidence: 99%